Ly antigens as markers for functionally distinct subpopulations of thymus-derived lymphocytes of the mouse. - Kisielow, P; Hirst, J; Shiku, H; Beverley, P; Hoffman, M; Boyse, E; Oettgen, H (1975)
From experiments with mice, it was shown that antisera to different Ly alloantigens can identify functionally distinct subpopulations of T cells (thymus derived lymphocytes).